PERBEDAAN KEMAMPUAN PEMECAHAN MASALAH DENGAN MENGGUNAKNA MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT DAN TIPE STUDENT TEAMS ACHIEVEMENT DIVISION - Rani Febriyanni Radhiatun Mardhiah (STAI Jama'iyah Mahmudiyah Tanjung Pura, 2021)
The purpose of this study was to determine the differences in students' mathematical problem-solving abilities taught by using the TGT and STAD cooperative learning models in the tangent circle material in class VIII MTs. Muallimin UNIVA Medan. This type of research is quantitative research, with the type of quasi-experimental research. The population is all students of class VIII MTs. Muallimin UNIVA Medan T.P 2015/2016. The sample in this study was class VIII-A and class VIII-B. Data collection techniques in the form of interviews, observation, documentation, and tests. Data analysis was performed with One Way Analysis of Variance (ANOVA). These findings indicate: 1) The mathematical problem solving abilities of students in class VIII A who are taught using the TGT cooperative learning model have fulfilled their mastery of learning in understanding problems, planning problem solving and implementing problem solving plans; 2) The mathematical problem solving abilities of students in class VIII B who are taught using the STAD cooperative learning model have fulfilled their mastery of learning in understanding the problem; 3) There are differences in students' mathematical problem solving abilities taught using the TGT cooperative learning model better than the STAD type in the tangent circle material in class VIII MTs. Muallimin UNIVA Medan.